2018
DOI: 10.1186/s13063-018-2578-7
|View full text |Cite
|
Sign up to set email alerts
|

Patient-centered recruitment and retention for a randomized controlled study

Abstract: BackgroundRecruitment and retention strategies for patient-centered outcomes research are evolving and research on the subject is limited. In this work, we present a conceptual model of patient-centered recruitment and retention, and describe the recruitment and retention activities and related challenges in a patient-centered comparative effectiveness trial.MethodsThis is a multicenter, longitudinal randomized controlled trial in localized prostate cancer patients.ResultsWe recruited 743 participants from thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 49 publications
1
58
0
Order By: Relevance
“…Therefore, we did not provide an active intervention such as communication training or instruction with the tablet to family caregivers beyond a simple instruction sheet. Despite best practices for participant retention strategies such as reminders, incentive payments, clear expectations of follow-up, and same interviewer used in throughout the study (Abshire et al, 2017;Chhatre et al, 2018;Dilworth-Anderson & Williams, 2004), our long-term retention rates were low. Family caregivers likely had competing priorities and this was confirmed during phone conversations with retained participants in which they revealed multiple caregiving responsibilities, serious financial concerns, rehospitalization, etc.…”
Section: Feasibility and Acceptabilitymentioning
confidence: 84%
See 1 more Smart Citation
“…Therefore, we did not provide an active intervention such as communication training or instruction with the tablet to family caregivers beyond a simple instruction sheet. Despite best practices for participant retention strategies such as reminders, incentive payments, clear expectations of follow-up, and same interviewer used in throughout the study (Abshire et al, 2017;Chhatre et al, 2018;Dilworth-Anderson & Williams, 2004), our long-term retention rates were low. Family caregivers likely had competing priorities and this was confirmed during phone conversations with retained participants in which they revealed multiple caregiving responsibilities, serious financial concerns, rehospitalization, etc.…”
Section: Feasibility and Acceptabilitymentioning
confidence: 84%
“…Additional participant retention strategies such as effective text reminders, increased amount of incentives, building relationship and identity, emphasizing study benefits, and contact/scheduling strategies (Chhatre et al, 2018;Dilworth-Anderson & Williams, 2004) should be considered in the future studies.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
“…The qualitative interviews were analysed using Braun and Clarke's framework for thematic analysis [29] using NVIVO version 10 (QSR International (UK) Ltd.). Transcripts were read and re-read and then coded inductively for themes relating to; reasons to participate in the trial, reasons not to participate in the trial, reasons to remain in the trial and reasons to discontinue the trial.…”
Section: Discussionmentioning
confidence: 99%
“…There is an increasing literature around person centeredness in trials with growing evidence that involving patients at the research design stage can direct recruitment and retention strategies and improve enrolment (26)(27)(28). While studies evaluating person-centred care in trials remain limited, Chhatre et al applied a conceptual model of patient-centred recruitment and retention to a RCT of patients with newly diagnosed prostate cancer (29). The study identified strategies which may aid recruitment and retention, although acknowledged limitations due to time and resource constraints, with attrition of 26% at one of three sites (29).…”
Section: Designmentioning
confidence: 99%
See 1 more Smart Citation